Social contacts and the economic performance of immigrants: A panel study of immigrants in Germany - Agnieszka Kanas; Barry R. Chiswick; Tanja van der Lippe; Frank van Tubergen (Institute for the Study of Labor (IZA), 2011)
Using data from the German Socio-Economic Panel, we examined the impact of social contacts on immigrant occupational status and income. In addition to general social contacts, we also analyzed the effects of bonding (i.e., co-ethnic) and bridging (i.e., interethnic) ties on economic outcomes. Results show that general social contacts have a positive effect on the occupational status and, in particular, annual income of immigrants. We also find that bridging ties with Germans lead to higher occupational status, but not to increased income. These effects remain visible even when social contacts are measured (at least) one year prior to the economic outcomes, as well as when earlier investments in German human capital are considered. Finally, we show that co-ethnic concentration in the region of residence weakly affects economic returns to German language proficiency and schooling.
urn:nbn:de:101:1-20110621347
Keywords: F22; J61; Z13; 330; immigrants; social contacts; occupational status; income; panel data